The same way you became Cesar." : Rome, power, literature and cinema. - Álvarez, José Maurício (Advances in Social Sciences Research Journal, 2021)
In this essay, we debate the image of the Roman Empire represented in films produced by mainstream Hollywood cinema, whose Jewish-Christian ideological matrix placed Rome as the image of evil instead of an excellent idea in the North American version. In contrast, we will analyze Fellini’s film Satyricon, which, distanced from the conventions of the historical film produced during the Cold War, created a dreamlike image of Rome and its Empire. Secondly, we will see the historical context of Petronius’ work situated at the end of the reign of Emperor Nero. At the time, diversified sexuality presented man’s power as a phallic power, which penetrates and rapes as a supremacy strategy. The Emperor is an actor-governor employing wiles and violence to reach the throne and maintain himself there. Petronius portrays the emergence of a new female sensuality whose morals oscillated between Vestal’s virginal purity, the wife’s pudititas, and sexual bestiality. At the same time, Fellini’s film recreates the cultural environment of the classical world shaped by literature and the image of the city of Rome as Cosmopolis or Anthopolis. The ambiguous characters move freely and incessantly through the corners of the Roman Empire. The struggle for power and the representations of pagan religiosity show human beings surrendered to their cunning as a strategy for survival and overcoming existential evils. In conclusion, we will see that both works, Petronius’ Satyrica and Fellini’s Satyricon, present themselves with their independent and intertwined narratives, composing the account of a journey like the Odyssey, metaphor of the incompleteness of human life and the impermanence of the sexual pleasure and the transience of power.